Presence of mycorrhizal fungi and a fluorescent iPseudomonas /i sp. in the rhizosphere of cacao in two agroecosystems and their effects on cacao seedling growth (2016)
In recent years the cultivation of cacao (Theobroma cacao L.) in Colombia has been growing up, resulting in the need to develop a sustainable production system. In this regard, beneficial soil microorganisms are an alternative for improving plant productivity, but this requires knowledge of their ecology and functioning. This study had the objective of identify and quantify arbuscular mycorrhizal fungi (AMF) and fluorescent Pseudomonas sp. associated with the soil and rhizosphere of cacao plants in two agroecosystems, one of them was in a tropical dry forest (TDF) and the other in a tropical moist forest (TMF). In a second stage of the study, native strains of Glomus sp., Acaulospora sp., and fluorescent Pseudomonas sp. were selected and multiplied in the lab. Subsequently, the effectiveness of these strains to promote cacao seedling growth was tested in a greenhouse experiment. The results indicate that there was a significant (P≤0.05) greater mycorrhizal colonization and diversity associated to the roots of cacao growing in agroecosystems of the tropical moist forest. However, not significant differences were detected regarding the presence of fluorescent Pseudomonas sp. in the two agroecosystems. Otherwise, in the greenhouse experiments, the inoculation with the mycorrhizal fungus Glomus sp. was the only treatment that promoted the cacao seedling growth.